Assessment of health-related quality of life of children with idiopathic nephrotic syndrome and their caregivers in China - Xia Wang; Danny Junyi Tan; Lejing Guan; Yifei Shao; Jingjing Wang; Chunyue Feng; Haidong Fu; Huijun Shen; Xiujuan Zhu; Abdul Rafay; Jianhua Mao; Guannan Bai (Health and Quality of Life Outcomes)
Abstract Aims The primary aim of this study was to characterize the health-related quality of life (HRQoL) and identify the associated factors among children aged 2 to 18 in China diagnosed with idiopathic nephrotic syndrome (INS). Additionally, the study aimed to evaluate the HRQoL and caregiving burden of their caregivers and investigate the correlation between the HRQoL of the children and that of their caregivers. Methods This study recruited 181 children diagnosed with INS from Children’s Hospital, Zhejiang University School of Medicine in China. The proxy-reported PedsQL Generic Core Module (PedsQL™ 4.0 GCM) was used to measure the HRQoL of children, and the EuroQol five-dimensional questionnaire, five-level version (EQ-5D-5L) was applied to measure caregivers’ HRQoL. Differences in scale scores and total scores of PedsQL™ 4.0 GCM were assessed using t-tests and one-way ANOVA. Multivariate linear regression analysis was used to identify the factors associated with children’s HRQoL. Pearson correlation analysis evaluated the correlation between children’s HRQoL and caregiver’s HRQoL. Results HRQoL of Children with INS declines with increasing age, and children aged 5-18 had lower scores in physical functioning, emotional functioning, school functioning, psychosocial health summary score, and total PedsQL™ 4.0 GCM score compared to healthy children. Various factors, including the mother filling out the questionnaire, the father being unemployed, and the use of other medications except for steroids, were associated with worse HRQoL of children (p values < 0.05). Additionally, a correlation exists between children’s HRQoL and their caregivers’ HRQoL. Conclusion This study evaluated the HRQoL of children aged 2-18 years diagnosed with INS in China, along with the HRQoL of their caregivers. Multiple factors potentially influence the HRQoL of children. A significant correlation was observed between the HRQoL of children and their caregivers, who frequently experienced varying levels of caregiving burden. Therefore, it is recommended that healthcare professionals prioritize optimizing HRQoL for children with INS and their caregivers.